2019
DOI: 10.3390/polym11060981
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Behavior and Tribological Properties of Polymer Brushes on Laser-Textured Surface

Abstract: Polymer brush layers can act as effective lubricants owing to their low friction and good controllability. However, their application to the field of tribology is limited by their poor wear resistance. This study proposes a strategy combining grafting and surface texturing to extend the service life of polymer brushes. Surface microstructure and chemical composition were measured through scanning electron microscopy (SEM), atomic force microscopy (AFM), and X-ray photoelectron spectroscopy (XPS). Water contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Among these techniques are electrochemical machining, micro-milling, ion-beam etching, hot embossing, lithography, mechanical texturing, and LST. A combination of grafting and texturing to improve the wettability and tribological properties of polymer brushes [6] was explored with the aim of prolonging their life. Results of the process showed that the micro-textures protected the brushes from wear and increased their tribological performance, hence extending their service life.…”
Section: Introductionmentioning
confidence: 99%
“…Among these techniques are electrochemical machining, micro-milling, ion-beam etching, hot embossing, lithography, mechanical texturing, and LST. A combination of grafting and texturing to improve the wettability and tribological properties of polymer brushes [6] was explored with the aim of prolonging their life. Results of the process showed that the micro-textures protected the brushes from wear and increased their tribological performance, hence extending their service life.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al presented a method to increase the lifetime and stability of a low-friction polymer layer by grafting chains onto a laser-textured surface. 72 The use of a micro-textured substrate enable protection of polymer chains and expands application possibilities. Inspired by natural lubricants, Rong et al designed a system that mimics articular cartilage, exhibiting extremely low friction even under high contact pressures.…”
Section: Lubricationmentioning
confidence: 99%
“…Another possible method is to increase the number of surface functional groups by anchoring polymeric chain on the surfaces. [34][35][36][37] There are several methods to anchor polymer chains on the surface, such as the grafting to (GT), grafting from (GF), and surface bounce methods.…”
Section: Introductionmentioning
confidence: 99%